Excessive potassium fertilization intensifies fruit cracking in litchi (Litchi chinensis) (Current Horticulture, 2024)
Potassium (K) nutrition is very important for high yield and quality of litchi (Litchi chinensis Sonn.) fruits. However, overdose of fertilizer K, especially when the application ratio of fertilizer N:K2O is